Pathomorphological characteristic of the impact of foam sclerosant on the venous wall in case of varicose disease - Yu. P. Titova (Patologìâ, 2014)
In treatment of varicose disease methods of intraoperative phlebosclerotic obliteration involving injection of sclerosant into vein lumen come to the fore. Issues of morphological changes in venous wall are actual and unstudied.